Lactate modulates the function of myeloid-derived suppressor cells via Ten-Eleven-Translocation-2-mediated demethylation of glucocorticoid-inducible kinase 1 in lung cancer model - Chu, Ying; Shen, Hua; Li, Qiu; Shen, Bo; Zhang, Yan; Wang, Deqiang; Zhu, Wei; Wang, Shengjun; Ma, Jie (Frontiers in Cell and Developmental Biology, 2025)
BackgroundLactate has been shown to play an important immunosuppressive role in the tumor microenvironment (TME) and promote tumor progression through a variety of different mechanisms of action. Myeloid-derived suppressor cells (MDSCs) are important cells that play an immunosuppressive role in the TME. However, the underlying mechanism by which lactate regulates MDSCs remains unclear. This study aims to explore the molecular mechanism by which lactate regulates the immunosuppressive function of MDSCs in the TME, providing new ideas and targets for anti-tumor immunotherapy targeting MDSCs.MethodsThis study used the Lewis lung carcinoma cell line to establish a subcutaneous lung cancer model; MDSCs were isolated from the spleens of these mice for subsequent experiments. Protein expression was analyzed by Western blot, mRNA expression by qRT-PCR, protein-DNA interactions by ChIP-qPCR, and DNA methylation by MSP-qPCR and BSP. Exploring the regulatory mechanism of CD38 on the immunosuppressive function of MDSCs by knockdown and overexpression techniques.ResultsWe found that compared with spleen-derived MDSCs (SP-MDSCs) of subcutaneous lung cancer model, tumor-derived MDSCs (T-MDSCs) had stronger immunosuppressive function. Lactate could promote the immunosuppressive function of MDSCs, significantly upregulate the expression of serum and glucocorticoid-inducible kinase 1 (SGK1) in MDSCs. Further studies demonstrated that lactate could downregulate the DNA methylation level of SGK1 by regulating the Ten-Eleven-Translocation-2 (TET2) and TET2 was closely related to the immunosuppressive function of MDSCs and the progression of tumors.ConclusionLactate can upregulate the expression of SGK1 through demethylation mediated by TET2, enhancing the immunosuppressive function of MDSCs to promote tumor progression. It provides the effective therapeutic targets for anti-tumor therapy.